2017
DOI: 10.1371/journal.pone.0178176
|View full text |Cite
|
Sign up to set email alerts
|

Wheat root length and not branching is altered in the presence of neighbours, including blackgrass

Abstract: The effect of neighbouring plants on crop root system architecture may directly interfere with water and nutrient acquisition, yet this important and interesting aspect of competition remains poorly understood. Here, the effect of the weed blackgrass (Alopecurus myosuroides Huds.) on wheat (Triticum aestivum L.) roots was tested, since a low density of this species (25 plants m -2 ) can lead to a 10% decrease in wheat yield and herbicide resistance is problematic. We used a simplified growth system based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Root length at the seedling stages of the plant is a key genetic trait for increasing yield under drought conditions (Shahbazi et al, 2012). Also, this trait was the most variable trait, as according to previous study the length of wheat seminal roots was mainly affected by the presence of another wheat plants (Finch et al, 2017) and that could be the case in the current research for the roots in petri dishes. 2011) applied both normal and water-deficient conditions to wheat genotypes and observed that genotypes performed better under environments which had optimum RWC and root and shoot length, which were considered droughttolerant genotypes.…”
Section: Agronomical and Morphological Traitssupporting
confidence: 57%
“…Root length at the seedling stages of the plant is a key genetic trait for increasing yield under drought conditions (Shahbazi et al, 2012). Also, this trait was the most variable trait, as according to previous study the length of wheat seminal roots was mainly affected by the presence of another wheat plants (Finch et al, 2017) and that could be the case in the current research for the roots in petri dishes. 2011) applied both normal and water-deficient conditions to wheat genotypes and observed that genotypes performed better under environments which had optimum RWC and root and shoot length, which were considered droughttolerant genotypes.…”
Section: Agronomical and Morphological Traitssupporting
confidence: 57%
“…Varying methods of planting have been utilized for gel-based systems to combat these problems. Studies utilizing gel-phenotyping have germinated seeds in Petri plates with media [85] or in nutrient solution [83] and have then inserted the seedlings into the gel for further growth. This method may artificially influence the root angle and can damage roots.…”
Section: Lab and Greenhouse-based Phenotyping For Root System Architementioning
confidence: 99%
“…The user has the option to review the automatic identification for each root segment to ensure an accurate measurement of the imaged root system [68]. SmartRoot has been used in wheat research to characterize germplasm [70,71], analyze plant-plant interactions [72], and study potential breeding targets for root architectural traits [73].…”
Section: Software Applicable To Root Phenotyping In Wheatmentioning
confidence: 99%